2022
DOI: 10.1073/pnas.2109617119
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein phosphorylation at serine 129 occurs after initial protein deposition and inhibits seeded fibril formation and toxicity

Abstract: Significance Converging evidence points to the build-up of phosphorylated α-synuclein (α-syn) at residue serine 129 (pS129) in Lewy body disease, suggesting its central role in the regulation of α-syn aggregation and neuronal degeneration. However, a comprehensive understanding of the role of α-syn phosphorylation at pS129 in α-synuclenopathies pathogenesis is still lacking. Herein, we study the phosphorylation incidence and its effect on α-syn aggregation propensity and cellular toxicity. Collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 60 publications
(76 reference statements)
5
56
0
Order By: Relevance
“…However, whether phosphorylation at S129 has causal roles in aggregation is not entirely clear [ 4 , 93 ]. Indeed, recent work suggests that phosphorylation of S129 occurs after more mature aggregation of the proteins [ 86 ] and that S129 phosphorylation may decrease aggregation of α-synuclein [ 55 ]. However, our results suggest that STI1 plays a role in vivo in S129 phosphorylation, but also facilitates α-synuclein inclusion deposition.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether phosphorylation at S129 has causal roles in aggregation is not entirely clear [ 4 , 93 ]. Indeed, recent work suggests that phosphorylation of S129 occurs after more mature aggregation of the proteins [ 86 ] and that S129 phosphorylation may decrease aggregation of α-synuclein [ 55 ]. However, our results suggest that STI1 plays a role in vivo in S129 phosphorylation, but also facilitates α-synuclein inclusion deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an in vitro study modelling BMAA consumption has demonstrated the structural destabilisation of SOD1 proteins following the substitution of any serine with BMAA, resulting in promotion of neurotoxic SOD1 aggregation [ 130 ]. Similarly, BMAA misincorporation in αSyn is thought to promote protein aggregation via the destabilisation of the extension in Serine 129 phosphorylation [ 123 ], the major posttranslational modification of αSyn aggregation [ 131 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…However, the extent to which these antibodies capture the full spectrum of aSyn pathology has not been systematically investigated. Furthermore, recent findings support a potentially protective effect of aSyn pS129 (Ghanem et al, 2022), and therefore the absence of this modification does not necessarily indicate the absence of aSyn pathology.…”
Section: Introductionmentioning
confidence: 96%